Intuition and social work practice: a different kind of knowing - Newburry-Kupe, Felicity J.; Napan, Ksenija (Taylor and Francis Group, 2025)
ABSTRACT This phenomenological, interpretive study sought to discover whether social workers in Aotearoa (New Zealand) integrated intuitive knowledge and experiences into their practice. The aim was to understand how this integration or non-integration impacted their practice and how their professional environments influenced their experiences. Through reflexive thematic analysis of interview transcripts, the findings gave insight into the practice of how four social workers utilized intuition in their professional practice. These findings included the impact of this integration and their professional environment on their personal and professional well-being and client outcomes.
Keywords: spirituality; intuition; social work